Diet, physical exercise and cognitive behavioral training as a combined workplace based intervention to reduce body weight and increase physical capacity in health care workers - a randomized controlled trial - Holtermann Andreas; Overgaard Kristian; Ekner Dorte; Faber Anne; Christensen Jeanette R; Søgaard Karen (BMC, 2011)
Abstract Background Health care workers comprise a high-risk workgroup with respect to deterioration and early retirement. There is high prevalence of obesity and many of the workers are overweight. Together, these factors play a significant role in the health-related problems within this sector. The present study evaluates the effects of the first 3-months of a cluster randomized controlled lifestyle intervention among health care workers. The intervention addresses body weight, general health variables, physical capacity and musculoskeletal pain. Methods 98 female, overweight health care workers were cluster-randomized to an intervention group or a reference group. The intervention consisted of an individually dietary plan with an energy deficit of 1200 kcal/day (15 min/hour), strengthening exercises (15 min/hour) and cognitive behavioral training (30 min/hour) during working hours 1 hour/week. Leisure time aerobic fitness was planned for 2 hour/week. The reference group was offered monthly oral presentations. Body weight, BMI, body fat percentage (bioimpedance), waist circumference, blood pressure, musculoskeletal pain, maximal oxygen uptake (maximal bicycle test), and isometric maximal muscle strength of 3 body regions were measured before and after the intervention period. Results In an intention-to-treat analysis from pre to post tests, the intervention group significantly reduced body weight with 3.6 kg (p < 0.001), BMI from 30.5 to 29.2 (p < 0.001), body fat percentage from 40.9 to 39.3 (p < 0.001), waist circumference from 99.7 to 95.5 cm (p < 0.001) and blood pressure from 134/85 to 127/80 mmHg (p < 0.001), with significant difference between the intervention and control group (p < 0.001) on all measures. No effect of intervention was found in musculoskeletal pain, maximal oxygen uptake and muscle strength, but on aerobic fitness. Conclusion The significantly reduced body weight, body fat, waist circumference and blood pressure as well as increased aerobic fitness in the intervention group show the great potential of workplace health promotion among this high-risk workgroup. Long-term effects of the intervention remain to be investigated. Trial registration ClinicalTrials.gov: NCT01015716